МНОГОЛЕТНЯЯ ДИНАМИКА ВСХОЖЕСТИ ЯИЦ АРТЕМИИ (ARTEMIA sp. ) ИЗ ОЗЕР СЕВЕРНОГО КАЗАХСТАНА (Eurasian Journal of Ecology, 2016)
In the article presented data’s by long experience of germination eggs of artemia from for lakes of north Kazakhstan. The data’s indicate that on long standing artemia embryo’s can viability.